Queer Farmers in the 2017 US Census of Agriculture. Issue 2 (1st February 2021) - Dentzman, Katherine; Pilgeram, Ryanne; Lewin, Paul; Conley, Kelsey
Abstract: Research suggests queer farmers are both more prevalent than expected and different from other farmers in significant ways. Using 2017 USDA Census of Agriculture data, we investigate this premise using an innovative coding scheme to identify two-producer farms run by men married to men and women married to women. Our findings suggest a good deal of farms are run by queer farmers and are they significantly different in several ways from non-queer farms. We encourage further investigation of queer farmers using USDA Census of Agriculture data and provide the coding scheme needed to do so. We further call for a refinement of the USDA Census of Agriculture question regarding marital status making it easier to identify producers married to each other, and subsequently same-sex married producers.